2022
DOI: 10.3390/agriculture12091354
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Mechanical Properties of Pumpkin Grafted Seedling Investigated by Finite Element Simulation and Experiment

Abstract: The cutting device in the seedling grafting process was studied, which provided a reference for optimizing the structural parameters and working parameters of important shearing components in the seedling grafting line, thereby improving the performance of the cutting device. The dynamic cutting process of the cutting device was numerically simulated. The effects of four factors, the average cutting speed (X1), the sliding angle (X2), the cutting edge angle (X3), and the cutter clearance (X4) on the cutting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We applied a gravitational force of 2.79 N under each planting cup and 6.71 N in the center of the cultivation plate. To ensure the accuracy of the simulation's calculations, this study used the Sweep function to partition the mesh and set the free form surface mesh type to Quad/Tri [36]. The mesh size at the handle was set to 1 mm and From the analysis of Figure 17, it can be seen that the maximum height changes of the center of mass were 0.04 mm, 0.65 mm, 1.80 mm, and 3.05 mm when the propulsion speed was increased from 0.2 m•s −1 to 0.5 m•s −1 .…”
Section: Static Analyses During the Output Of The Cultivation Platementioning
confidence: 99%
See 1 more Smart Citation
“…We applied a gravitational force of 2.79 N under each planting cup and 6.71 N in the center of the cultivation plate. To ensure the accuracy of the simulation's calculations, this study used the Sweep function to partition the mesh and set the free form surface mesh type to Quad/Tri [36]. The mesh size at the handle was set to 1 mm and From the analysis of Figure 17, it can be seen that the maximum height changes of the center of mass were 0.04 mm, 0.65 mm, 1.80 mm, and 3.05 mm when the propulsion speed was increased from 0.2 m•s −1 to 0.5 m•s −1 .…”
Section: Static Analyses During the Output Of The Cultivation Platementioning
confidence: 99%
“…We applied a gravitational force of 2.79 N under each planting cup and 6.71 N in the center of the cultivation plate. To ensure the accuracy of the simulation's calculations, this study used the Sweep function to partition the mesh and set the free form surface mesh type to Quad/Tri [36]. The mesh size at the handle was set to 1 mm and the other parts were set to 3 mm, with a total of 395,322 nodes and 203,811 meshes.…”
Section: Static Analyses During the Output Of The Cultivation Platementioning
confidence: 99%
“…Daipeng Lu, Wei Wang, et al, 2022, in the course of multifactorial orthogonal experiment and mathematical modeling established the factors that affect the cutting stress: sliding angle, cutting edge angle, cutting speed. It was found that the factor of greatest importance is the sliding angle.…”
Section: Fig 1 -Sunflower Stubblementioning
confidence: 99%
“…Tian et al selected the range of rootstock and scion cutting angles based on their experience, designed a rotary cutting mechanism, and obtained the optimal parameter combination of cutting radius, cutting speed, and cutting angle [14]. Lu et al investigated the effects of the sliding cutting angle, cutting edge angle, and average cutting speed on cutting energy consumption and determined the order in which each factor affects the significance of cutting stress [15]. Jiang et al performed parameter optimization of the rotary cutting mechanism to change the cutting angle by adjusting the spatial position of the center of rotation of the cutter.…”
Section: Introductionmentioning
confidence: 99%